Impacto da criação da Associação Brasileira de Medicina Diagnóstica (ABRAMED) como estratégia de competitividade no setor privado de serviços diagnósticos no Brasil - Melo Junior, Marco Antonio Cezario de (2018)
ABRAMED (Brazilian Association of Diagnostic Medicine) was founded through the convergence of the interests of the largest diagnostic services companies in Brazil and through the mechanisms of action policies inherent to an association, contributes to the development of the sector it represents. ABRAMED's historical analysis demonstrates the importance of this association in the health value chain of diagnostic medicine. In this way, the healthcare market gains in competitiveness, process performance and better costeffectiveness. Great achievements have been catch up through ABRAMED's work in many areas with its specialized chambers and focused on themes such as technical, legal and, more recently, the communications group, which perform specific functions. Politicaleconomic, regulatory, legal, and fiscal actions, including interlocution with other sectors of society, such as the press, have resulted in a significant sequence of achievements for the health sector. The ABRAMED has been a player in the inclusion of new procedures in the roll of procedures of the National Agency of Supplementary Health, assisted the Federal Medical Council in understanding the technical responsibility of diagnostic medicine establishments, and emphasized to the Federal Medical Council the importance of the regionalization of the medical work by state of origin, so that there could be pathological evaluations on samples or even medical images originating from other federation states. The ABRAMED also assisted the National Sanitary Surveillance Agency in discussing the safety of biological material transportation, reprocessing of medical materials, and digital certification of examination reports. Nevertheless, the ABRAMED was a technical benchmark helping the legal positioning regarding tax and labor processes, given the association's expertise in the production and safety chain of the sector's workers. Each day, diagnostic medicine has been gaining strength and solidity through the Brazilian Association of Diagnostic Medicine, which has been fulfilling its objectives in defense of its members' wishes, in institutional affirmation, in the technical and scientific improvement of the sector and in excellence of diagnostic services for the quality of services rendered to the patient.